2020
DOI: 10.1038/s41419-020-02901-3
|View full text |Cite
|
Sign up to set email alerts
|

Hippo/MST blocks breast cancer by downregulating WBP2 oncogene expression via miRNA processor Dicer

Abstract: WBP2 transcription coactivator is an emerging oncoprotein and a key node of convergence between EGF and Wnt signaling pathways. Understanding how WBP2 is regulated has important implications for cancer therapy. WBP2 is tightly controlled by post-translational modifications, including phosphorylation and ubiquitination, leading to changes in subcellular localization, protein-protein interactions, and protein turnover. As the function of WBP2 is intricately linked to YAP and TAZ, we hypothesize that WBP2 is nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…However, the underlying cause of high WBP2 expression in lung cancer remains unclear. Based on existing literature, WBP2 expression could be affected by several underlying factors, including non-coding micro-RNA 30 , transcriptional factors 31 , and ITCH 32 , as well as some classical signaling transduction pathway activities 33 . These experimental data have helped clarify the reasons for high WBP2 expression in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying cause of high WBP2 expression in lung cancer remains unclear. Based on existing literature, WBP2 expression could be affected by several underlying factors, including non-coding micro-RNA 30 , transcriptional factors 31 , and ITCH 32 , as well as some classical signaling transduction pathway activities 33 . These experimental data have helped clarify the reasons for high WBP2 expression in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, changes in the activity of some classic signaling pathways can play an important role in regulating the expression of WBP2. For example, MST in the Hippo pathway can regulate the expression of WBP2 through the miRNA-Dicer pathway in a kinase-dependent manner [34].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism underlying the function of WBP2 in breast cancer is closely related to the steroid hormone signaling pathway (ER-based). Some scholars have determined that WBP2 is also the key node of the PI3K and Wnt signaling transduction pathways in other tumors [14,18,29], and WBP2 also plays a key role in the Hippo pathway [34]. Both Yki/YAP and TAZ in the Hippo signaling pathway are vital binding proteins of WBP2, as the binding of these proteins facilitates the transcription of downstream target genes and affects the development of Drosophila and the proliferation and invasion of tumor cells [8-9, 16, 19-20].…”
Section: Discussionmentioning
confidence: 99%
“…A number of miRNAs have also been identified to regulate WBP2 at the post-transcriptional level. For example, the 39UTR region of WBP2 has been demonstrated to be targeted by miR-206, miR-613, and miR-23a in breast cancer (11,15,16), and miR-458 in hepatocellular carcinoma (17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these core components, a number of auxiliary molecules have been recently reported to be important in the processing of Pri-miRNAs into Pre-miRNAs, for example, BRCA1 (23), Smads (24), Myc (25), and p53 (26). Recently, our laboratory showed that WBP2 is regulated by both 39UTR and coding DNA sequence-targeting miRNAs and that Dicer or DGCR8 modulates WBP2 expression under the influence of mammalian sterile 20-like (MST)/Hippo signaling (16). Taken together, we hypothesize that WBP2 regulates miRNA biogenesis via a negative feedback loop.…”
Section: Introductionmentioning
confidence: 99%